Analis terhadap Pandangan Janda tentang Poligami (Studi Kasus Desa Racek Kecamatan Tiris Kabupaten Probolinggo) - Nanang Qosim (Fakultas Syariah Institut Ilmu Keislaman Zainul Hasan, 2017)
Wedding or marriage in Arabic literature jurisprudence referred to by two words, namely marriage and zawaj. Both of these words are used in everyday life of Arabs and many contained in the Qur’an and the hadith of the Prophet. In Arabic, polygamy is called al-zawjah ta’did (couples), in the Indonesian language is called polygyny and in Sundanese called nyandung. According to the teachings of Islam, later called the Islamic Shari’a (Islamic law), defined as the act of polygamy is allowed or permissible. Thus, although in Surat an-Nisa ‘paragraph 3 sentence “fankihu”, the sentence amr (command) of the gainful permissible rather than mandatory, which can relevanced with usul fiqh: al-asl fi al-amr al-Ibahah Hatta Yadula’ ala at- Tahrim (origin of something may be, unless there is the argument that forbid).